SST Retrieval Using AVHRR on Board NOAA-19 in the Seas Around Japan - Anindya Wirasatriya; Hiroshi Kawamura; Futoki Sakaida (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2009)
The purpose of this study is to derive new Multi-Channel Sea Surface Temperature (MCSST) equations of AVHRR aboard NOAA-19, which was launched in February 2009.  Since the HRPT data transmitted from the satellite are directly received at the Tohoku University in Japan, the study area is the seas surrounding it.  Using in situ SSTs measured by drifting buoys, 2248 match-ups (1181 for daytime and 1067 for nighttime) are generated for September - November 2009. The daytime and nighttime match-ups are separated into a half for algorithm tuning and another half for validation.  Coefficients of MCSSTs are obtained for daytime and nighttime by applying multiple regression analysis to the match-ups, which consist of brightness temperatures of the AVHRR split-window channels and the in-situ SSTs. Validation using the independent match-ups shows that the retrieved daytime and nighttime SSTs have biases of 0.05 and 0.08°C and root mean square differences of 0.61°C and 0.55°C, respectively. Key words :  AVHRR, MCSST, NOAA-19, seas around Japan  Tujuan dari kajian ini adalah untuk memperoleh formula Multi-Channel Sea Surface Temperature (MCSST) baru dari AVHRR/NOAA-19 yang diluncurkan pada bulan February 2009. Karena HRPT data yang ditransmisikan dari satelit diterima di Universitas Tohoku, Jepang maka area kajiannya adalah perairan di sekitar Jepang. Dengan menggunakan pengukuran SST in-situ yang didapat dari drifting buouys , sebanyak 2248 match-up data (1181 untuk siang hari dan 1067 untuk malam hari) diperoleh dari data bulan September-November 2009. Kemudian match-up data tersebut dipisahkan menjadi 2 bagian, separuh digunakan untuk mendapatkan formula dan separuhnya lagi untuk validasi. Koefisien formula MCSST diperoleh menggunakan analisa multi regresi terhadap match-up data yang terdiri dari brightness temperature dari kanal AVHRR split window dan SST in-situ. Validasi menggunakan match-up data independen menunjukkan untuk siang hari nilai SST memiliki bias 0.05°C dan Root mean square differences (RMSD) sebesar 0.610C sedangkan untuk malam hari sebesar 0.08°C untuk bias dan 0.55°C untuk RMSD. Kata kunci : AVHRR, MCSST, NOAA-19, perairan Jepang